3-D magnetic graphene oxide-magnetite poly(vinyl alcohol) nanocomposite substrates for immobilizing enzyme. (1st August 2018) - Li, Yanyun; Jing, Tao; Xu, Gaofeng; Tian, Jingzhi; Dong, Mengyao; Shao, Qian; Wang, Bin; Wang, Zhikang; Zheng, Yongjie; Yang, Changlong; Guo, Zhanhu
Abstract: Three-dimensional magnetic graphene oxide-magnetite polyvinyl alcohol (3D-GO/PVA/Fe3 O4 ) nanocomposites were successfully prepared. The morphology was characterized and analyzed through scanning electron microscope (SEM) and transmission electron microscope (TEM). The chemical structure and the crystal structure were explored by X-ray powder diffraction (XPS), Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction spectra (XRD). The magnetic property was obtained by vibrating sample magnetometer (VSM). The specific surface area and the average pore size were determined by Brunauer-Emmett-Teller (BET) and Barrett–Joyner–Halenda (BJH). The specific surface and the average pore size of 3D-GO/PVA/Fe3 O4 nanocomposites were 388.87 m 2 g -1 and 9.6 nm, and the higher specific surface indicated that the three-dimensional structure avoided the aggregation for GO sheets. The large saturation magnetization (Ms ) of the nanocomposites of 30.5 emu/g enabled the easy cycling of the nanocomposites. The 3D-GO/PVA/Fe3 O4 nanocomposites exhibited better performance for porcine pancreatic lipase (PPL) enzyme immobilization. The maximum immobilization efficiency was 91%, and the enzyme immobilized 3D-GO/PVA/Fe3 O4 nanocomposites reached up to 90% of their activities. After 10 cycles of reuse, the activity of immobilized enzyme remained about 70.8% of the initial activity. The stability test revealed that the activity of immobilized enzyme remained up to 71.1% at 4 °C for 56 days. Graphical abstract: Image 1 Highlights: Three-dimensional network structure prevented GO from agglomeration. Hydroxyl-rich PVA provided more binding sites for immobilizing enzyme. The best immobilized efficiency for (3D-GO/PVA/Fe3 O4 )-PPL (91%) was much higher than that for (GO/Fe3 O4 )-PPL (76%). The immobilized enzyme exhibited high stability.